Vertical and horizontal ridge augmentation in anterior maxilla using autograft, xenograft and titanium mesh with simultaneous placement of endosseous implants - Deshpande, Sudhendra (J Indian Soc Periodontol, 2014)
Endosseous implants have revolutionized the field of Implants and Periodontics. Implant placement is a viable option in the treatment of partial and full edentulism. However, placement of implants in alveolar deficiencies may lead to adverse angulations, mechanical overload and esthetic dissatisfaction. When minimum dimensions for implant placement are not present in alveolar process, it is necessary to augment the size of the ridge. This can be achieved by various methods and materials. Here we present a successful case of vertical and horizontal ridge augmentation in anterior maxilla using autograft, xenograft and titanium mesh with simultaneous placement of implants, where autograft was obtained from the same site avoiding secondary surgical site.